2015
DOI: 10.1016/j.neurobiolaging.2015.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinase 9–mediated intracerebral hemorrhage induced by cerebral amyloid angiopathy

Abstract: Cerebral amyloid angiopathy (CAA), the deposition of β-amyloid (Aβ) in cerebrovascular walls, is the most common cause of lobar hemorrhagic stroke. Previous studies show that cerebrovascular Aβ induces expression and activation of matrix metalloproteinase 9 (MMP-9) in cerebral vessels of amyloid precursor protein (APP) transgenic mice. Here we extended these findings and evaluated MMP-9 expression in postmortem brain tissues of human CAA cases. MMP-9 co-localized with CAA, correlated with the severity of the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 43 publications
1
29
0
Order By: Relevance
“…Of the sixteen included studies, one assessed BBB dysfunction in HV-related ICH ( n = 82) ( 36 ) six in CAA-related ICH ( n = 117) ( 37 42 ), and nine did not specify the underlying etiology of the ICH ( n = 489; Tables 2A , 2B , S4 ) ( 44 52 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the sixteen included studies, one assessed BBB dysfunction in HV-related ICH ( n = 82) ( 36 ) six in CAA-related ICH ( n = 117) ( 37 42 ), and nine did not specify the underlying etiology of the ICH ( n = 489; Tables 2A , 2B , S4 ) ( 44 52 ).…”
Section: Resultsmentioning
confidence: 99%
“…Of six studies that assessed CAA-related BBB dysfunction, five studies found evidence for ICH-associated BBB dysfunction. Three studies assessed BBB abnormalities as defined by altered gelatinase levels in cortical vessels ( 38 , 42 ), cerebral tissue ( 38 ), plasma ( 38 ), and CSF ( 41 ), in patients with CAA. The first study identified an increased percentage of MMP-2 positive cortical vessels in moderately to severely Aβ affected vessels from CAA patients compared with not to mildly affected cortical vessels of the same patients ( n = 6) and cortical vessels of non-CAA controls ( n = 3).…”
Section: Resultsmentioning
confidence: 99%
“…Microglial activation results in the production of matrix metalloproteinases (MMPs), a family of potent proteinases involved in remodeling of extracellular matrix and regulation of the BBB. 69 Secretion of MMPs has been observed in the perihematomal region in experimental models of ICH, [70][71][72][73][74] as well as in patients after hemorrhage. 72,75 These studies have found that MMP9 is particularly important for disruption of endothelial tight junctions, BBB remodeling, and increased vascular permeability after ICH, and high serum levels of MMP9 in ICH patients are associated with hematoma growth and poor clinical outcome.…”
Section: Production Of Inflammatory Factorsmentioning
confidence: 99%
“…27,[30][31][32] Deregulation of matrix metalloproteinases (MMP), specifically the MMP-9 species, has been suggested as an important contributor to CAA-associated hemorrhage. 33 These structural alterations likely affect vessel physiological function as well. 34 Ex vivo studies with isolated cerebral arterioles have shown that synthetic Aβ40 (and to a lesser degree Aβ42) induced direct vessel constriction, enhanced response to vasoconstrictors, and reduced response to vasodilators.…”
Section: Pathophysiologymentioning
confidence: 99%